Influential Factor of Temperature on Synthesis of L-Arginine Oligo-Peptides Mediated by Phosphorus Oxychloride - Ma1, L.; Zhao1, D.X.; Ren1, H.P.; Lu1, K. (Asian Journal of Chemistry, 2011)
Electrospray ionization mass spectrometry (ESI-MS) is one of the most widely applicable bio-MS technologies, with the characteristics of no fragmentation. Electrospray ionization mass spectrometry has proven to be an extremely powerful technique for the analysis of involatile, polar and thermally labile compounds which exist as ions (positive and negative) in solution. In this paper the effect of temperature on L-arginine self-assemble into oligo-peptides which analyzed by ESI-MS mediated by phosphorus oxychloride was investigated. The structure of Arg-Arg dipeptide was confirmed and the fragmentation pathway of Arg-Arg dipeptide was analyzed by ESI-MS/MS.